Optimizing Production Planning of PT Soraya Berjaya Indonesia - Wardani, Rahmi; Nizar, Adirizal (The Indonesian Journal of Business Administration, 2017)
Abstract - Production planning is one of the important factors to run business company. One of production planning is determine the product combination which will be produced in order to optimize the production capacity to fulfil the market demand by considering the availability of the resources. The instability of total products demand cause production planning changes every week. The first thing to do is identifing the product combination which will be produced. The product combination can be determined by using linear programming method. The aim of linear programming method is to determine the product combination which will be produced. Therefore, the company can optimize the production capacity of the company to get maximum revenue. If the company is not able to fulfil all demand, the company can do outsourcing production. Outsourcing production is the act of moving some of a firm’s internal activities to outside provider. But the weakness of outsourcing production is a lack of communication between the company and the outsourced provider may occur production delay and the quality of the product is not necessarily the same as the company's quality standards. Therefore, the company must maximize the use of production capacity first, then it could use outsource production.Keywords: Linear Programming, Outsourcing Production, Production Planning, Production Capacity